Falsafah Akal Al-Dihlawi: Analisis Aspek Prinsip dan Hakikat Berfikir Kritis dalam Hujjah Allah al-Balighah: The Philosophy of Intellect by Al-Dihlawi: An Analysis of the Principles and Essence of Critical Thinking in Hujjah Allah Al-Balighah - Junoh, Noraini; Mat Zin, Mohd Nazri; Mustapha, Ahmad Murshidi; Mohamad, Abdul Manam (Afkar: Jurnal Akidah dan Pemikiran Islam, 2024)
The intellect holds a crucial role in the Islamic worldview and is a prerequisite for the acceptance and fulfillment of all religious obligations. In fact, if a person loses their mental capacity, they are exempt from fulfilling these responsibilities. Today’s globalized world exposes Muslims to various worldviews, including secularism, liberalism, and pluralism, which can influence their thinking. This study aims to analyze al-Dihlawi’s philosophy of reason as presented in the book Hujjah Allah al-Balighah and its relationship with the principle of critical thinking. This study utilizes content analysis to explore al-Dihlawi’s thoughts on the relationship between the mind, heart, and nafs as presented in Hujjah Allah al-Balighah. Through his work, al-Dihlawi argues that these three elements are interdependent and contribute to the emergence of maqamat and ahwal. Moreover, his philosophy emphasizes the importance of nurturing the malakiyyah character over the bahimiyyah character, which involves cultivating a strong connection between the mind and soul. These insights offer valuable contributions to the spiritual structure of Islam, as they can facilitate an individual’s journey toward happiness and deeper knowledge of Allah SWT.